PENGARUH KEPEMIMPINAN KEUCHIK TERHADAP EFEKTIVITAS PELAYANAN MASYARAKAT DI GAMPONG KUMBANG KECAMATAN MILA - Zulfikar Zulfikar; Rozaili Rozaili; Zulkifli Zulkifli (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The aim of this research is to determine the influence of keuchik leadership on the performance of community services in Gampong Kumbang, Mila District. The method used in this research is qualitative, which examines the various influences of keuchik leadership on community services. Community service is one of the important things that a keuchik or village head must pay attention to when they lead the progress of the gampong. Analysis of the influence of leadership on the effectiveness of services to the Gampong Kumbang community, Mila District, was carried out through direct interviews with members of the Gampong Kumbang community, Mila District regarding infrastructure development, enforcement of Islamic law, and dispute resolution. The results of the interview show that the influence of Keuchik's leadership on the effectiveness of community services in Gampong Kumbang, Mila District is in the overall service sector, and the respondents' answer to this was that they gave good answers. and it is very good, only some people think it is not good. It is known that in society there are pros and cons to keuchik leadership. It is hoped that the people of Gampong Kumbang, Mila District will be more concerned about the performance of the keuchik and the Gampong apparatus by looking at previous progress and comparisons.